Responsive turns in Indonesian informal conversation - van Naerssen, M. J. (Wacana, Journal of the Humanities of Indonesia, 2015)
People have all sorts of expectations about how interlocutors will and should behave linguistically when engaged in a conversation. These conversational norms are usually implicit and are sometimes difficult to master in a language that is new to you. This paper presents a model of different types of responses in informal conversation, illustrated with Indonesian examples. It builds upon the conversation analytic notion of preference; distinguishing preferred - or constructive - responses and dispreferred - or competitive - responses. The model is meant as a tool to cross-linguistically compare response behaviour to gain insight in language specific expectations about interaction in informal conversation.